The Portrayal of Women in Katy Perry’s Selected Song Lyrics - Amelia Lisara (Universitas Pendidikan Indonesia (UPI), 2014)
The present study entitled The Portrayal of Women in Katy Perry’s Selected Song Lyrics aims at drawing the portrayal of women in the selected song lyrics and revealing gendered messages in the selected song lyrics as viewed in post feminism perspectives. Utilizing a qualitative research particularly descriptive method, the discussion of the present study is framed within gender studies and theory of post feminism. The result of the present study shows that most of women in One of the Boys album (2008) are portrayed through five portrayals highlighting women’s physical appearance, women as sexual subject, women’s passive behavior, and women’s attitudes to cover their dependency on men. These portrayals support patriarchal ideology in which women are in accordance with patriarchal society’s expectation. The present study also discovers that gendered messages in most of song lyrics in One of the Boys do not show the notion of post feminism by being passive and dependent to men. Nevertheless, several songs explore the theme of sexuality as one of feminism values.Keywords: Gender, Feminism, Ideology, Women